2016
DOI: 10.1089/brain.2015.0407
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle and Hormonal Contraceptive-Dependent Changes in Intrinsic Connectivity of Resting-State Brain Networks Correspond to Behavioral Changes Due to Hormonal Status

Abstract: Menstrual cycle-dependent changes have been reported for a variety of functions, including cognition, attention, emotion, inhibition, and perception. For several of these functions, an effect of hormonal contraceptives has also been discussed. Cognitive, attentional, emotional, inhibitory, and perceptual functions have been linked to distinct intrinsic connectivity networks during the resting state. However, changes in resting-state connectivity across the menstrual cycle phase and due to hormonal contraceptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…Inferences drawn from findings obtained in women herein therefore cannot be directly translated to men suffering from IBS. Recent findings further suggest an influence of menstrual cycle phase and intake of oral contraceptives on rsFC in women (Petersen et al, 2014, Pletzer et al, 2016). While excluding time of menses, females independent of hormonal status were included in the current study.…”
Section: Discussionmentioning
confidence: 91%
“…Inferences drawn from findings obtained in women herein therefore cannot be directly translated to men suffering from IBS. Recent findings further suggest an influence of menstrual cycle phase and intake of oral contraceptives on rsFC in women (Petersen et al, 2014, Pletzer et al, 2016). While excluding time of menses, females independent of hormonal status were included in the current study.…”
Section: Discussionmentioning
confidence: 91%
“…Some studies have shown that functional connectivity within the DMN is related to sleepiness (Ward et al, 2013) and is diminished after sleep deprivation (De Havas, Parimal, Soon, & Chee, 2012). Other studies found an influence of female hormones on functional connectivity during rest (e.g., Pletzer, Crone, Kronbichler, & Kerschbaum, 2016). Second, between-subject fluctuations in connectivity might be explained by differences in regional or global noise.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, they report changes in how networks are related to particular nodes, or regions, as a function of menstrual cycle phase. For instance, there is some suggestion that regions within the DMN appear more connected when hormones are low (early follicular phase), whereas regions within control networks appear more connected when progesterone or both progesterone and estradiol are high (midluteal phase) . But this is not always the case, as greater control‐related connectivity in the early follicular phase (i.e., low hormones) and complex patterns of correlations between estradiol and progesterone in several different networks, including the DMN, have been reported .…”
Section: Menstrual Cyclementioning
confidence: 99%
“…Some studies report no differences between women using OCs and naturally cycling women, whereas others report conflicting effects. For instance, compared with naturally cycling women, there is indication that women using OCs have reduced connectivity in DMN regions, but that women using androgenic OCs have greater connectivity in different DMN regions . There is similar confusion between studies when comparing active versus placebo phases in the frontoparietal network.…”
Section: Hormonal Contraceptivesmentioning
confidence: 99%